Fetal Deaths in SARS-CoV-2-Infected Pregnant Women: A Portuguese Case Series - Ana Rita Mira; João Pedro Pereira; Catrine Dahlstedt-Ferreira; Margarida Enes; Hélder Oliveira Coelho; Ana Beatriz Godinho (Case Reports in Obstetrics and Gynecology)
Introduction. Stillbirth has been documented as an outcome of SARS-CoV-2 infection in pregnancy. Placental hypoperfusion and inflammation secondary to maternal immune response seem to play a role in the cascade of events that contribute to fetal death. The aim of our study is to report a perinatal outcome of SARS-CoV-2 infection in pregnancy adding information to the pool of data on COVID-19 pregnancy outcomes. Case Presentation. This is the first stillbirth case series occurring in pregnant women infected with SARS-CoV-2 in a Portuguese cohort. Between April 2020 and March 2021, we had 2680 births in our centre, of which 130 (4.95%) involved mothers infected with SARS-CoV-2. Of total births, there were 14 stillbirths (0.52%), accounting for the highest stillbirth rate we have had in the last 5 years. Among these 14 stillbirths, 5 (35.71%) occurred in SARS-CoV-2-infected mothers. We report the clinical features and placental histopathologic findings of 4 stillbirth cases that occurred in our hospital. Discussion. The stillbirth rate among SARS-CoV-2-infected pregnant women (5/130; 3.84%) was significantly increased compared to noninfected patients (9/2550; 0.35%). Most women (3/4) were asymptomatic for COVID-19, a surprising outcome, given the current literature. All cases had histologic exams showing placental signs of vascular malperfusion, although we acknowledge that 3/5 had obstetric conditions related to placental vascular impairment such as preeclampsia and HELLP syndrome. Conclusion. Stillbirth can be a perinatal consequence of SARS-CoV-2 infection in pregnancy, even in asymptomatic patients. We urge more studies to explore the association between SARS-CoV-2 infection and the risk of stillbirth.